The use of PDV to understand damage in rocket motor propellants - Tear,GR; Chapman,DJ; Proud,WG; Ottley,PR; Cullis,IG; Gould,PJ; Jones,AW (AIP Publishing, 2018)
Photonic Doppler Velocimetry (PDV) has been fielded on small scale fragment impact experiments on double base propellant. A 130 mm block of propellant was impacted with a 20 mm diameter cylinder at 1003 ± 10 m s-1 and four PDV probes recorded rear surface motion at different radial distances between 10 mm and 60 mm from impact centre. The PDV was fielded alongside high speed video diagnostics using a dichroic mirror which reflected visible light whilst transmitting the 1550 nm wavelength which the PDV operated at. The rear surface velocity was compared to 2D numerical simulations of the experiment and found to be in good agreement. Additional material moving at up to 2 km s-1 was detected at break out.